Reparación y puesta en funcionamiento del centro de mecanizado CNC marca paxton patterson del laboratorio de control y automatización de la universidad Antonio Nariño sede Bogotá sur. - Tejada García, Andrés Felipe; Cubillos Cruz, Jesús David (Universidad Antonio Nariño, 2021)
This project seeks to put into operation the Paxton Patterson CNC machining center at the Antonio Nariño University in southern Bogotá, which has not been functional for approximately ten years due that it does not have the original software or communication hardware to operate this equipment. The proposal is to update mill machine with mach3 software, which is a software used to interpret the G code provided by CAD - CAM programs, the latter being responsible for the design of the parts, the layout of trajectories and the type of cutting tools to be implemented in milling machines. The mach3 has a user-friendly and easy to operate interface. This upgrade task involves changing the machine's driver which has to be compatible with the mach3 software. Improvements such as automatic opening and closing of the door will be implemented in order to avoid accidents during the operation of the equipment.